Penerapan Penganggaran Berbasis Kinerja Dalam Rangka Mewujudkan Good Financial Governance - Mulyono, Antonius Adikusuma; Hertianti, Ayuningtyas (Program Studi Akuntansi FPEB UPI, 2019)
Abstract. Financial reform mandates the importance of good financial governance, one of which is performance budgeting. The performance budgeting system is very concerned about the relationship between funding (input) and performance (output). The root of the problem in this study is the inconsistency between budget realization (92.72%) and output achievements (75%) in the implementation of performance budgeting in the Indonesian Ministry of Industry. This study aims to analyze the root causes of the problem. The theory of New Public Management (NPM) is used to see whether performanc budgeting is in accordance with the characteristics of the NPM, as measured by budget realization compared to the output achievements. The research approach is qualitative with a single case study method at the Indonesian Ministry of Industry. The results of the study show (1) the budget does not focus on supporting outputs but is used for other activities; (2) the targets set is not on target.These results indicate that the implementation of performance budgeting in the central government, especially in the Indonesian Ministry of Industry, has not been maximized and there are still several obstacles that have not been able to improve good financial governance. Keywords. Performance budgeting; good financial governance; and new public management.Abstrak. Reformasi keuangan negara mengamanatkan pentingnya good financial governance, salah satunya adalah penganggaran berbasis kinerja. Sistem penganggaran berbasis kinerja sangat memperhatikan keterkaitan antara pendanaan (input) dengan kinerja (output). Akar permasalahan dalam penelitian ini adalah adanya inkonsistensi antara realisasi anggaran (92,72%) dengan capaian output (75%) dalam penerapan penganggaran berbasis kinerja di Kementerian Perindustrian. Penelitian ini bertujuan untuk menganalisis penyebab akar permasalahan. Teori New Public Management (NPM) digunakan untuk melihat apakah penerapan penganggaran berbasis kinerja telah sesuai dengan karakteristik NPM, yang diukur dari realisasi anggaran dibandingkan dengan capaian output. Pendekatan penelitian adalah kualitatif dengan metode single case study di Kementerian Perindustrian. Hasil penelitian menunjukkan (1) anggaran tidak fokus mendukung output tetapi digunakan untuk kegiatan lainnya; (2) target yang ditetapkan tidak tepat sasaran.Hasil tersebut menunjukkan penerapan penganggaran berbasis kinerja di pemerintah pusat terutama di Kementerian Perindustrian belum maksimal dan masih terdapat beberapa kendala sehingga belum dapat meningkatkan good financial governance.Kata kunci. Â Penganggaran Berbasis Kinerja; Tata Kelola Keuangan Pemerintah yang Baik; New Public Management.